ANALISIS PENERIMAAN DAN PENGGUNAAN TEKNOLOGI GOOGLE DRIVE SECARA BERKELANJUTAN PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIKA ATMA JAYA JAKARTA - Erawan, Yossie; Pambudi, Rilo (Universitas Katolik Indonesia Atma Jaya, 2017)
The purpose of this research is to know satisfaction and attitude from Fakultas Ekonomi Unika Atma Jaya students using Cloud Computing Technology (Google Drive) and this continuance effect. This research using “Technology Continuance Theory” to evaluate The effect factors for continuance using Google Drive. This research using Non-Probability Sampling and using Questioners for gathering data. Object research is Fakultas Ekonomi Unika Atma Jaya students that using Google Drive. There’s 108 data gathered and processed using SPSS 21. The output for this research shows that Perceived Usefulness and Perceived Ease of Use bring positive effect for Attitude. Confirmation bring positive effect for Satisfaction. Satisfaction and Attitude bring significant effect for Google Drive Continuance Usage Intentions.